'Luk pe Coo, ' or Compensation as Dowry? Gendered Reflections on Reparations for Conflict-Related Sexual Violence against Men. (29th October 2018) - Schulz, Philipp
Abstract∞ : This Note explores a divergent viewpoint on reparations represented by a small group of male survivors of conflict-related sexual violence in Northern Uganda. According to this perspective, reparative justice measures equal the payment of dowry, locally conceptualized as luk . In this reading, reparations, if regarded as dowry, further cement survivors' perceived inferior subject positioning in a gendered manifestation and as previously initiated through the sexual violations. If viewed as dowry, reparations can thus entrench further gendered harms, rather than redressing suffering and vulnerabilities. These findings stand in contrast to how the relationships between reparations, victimhood and gender are commonly theorized, thus implying novel empirical and conceptual implications for gender-sensitive reparations in response to conflict-related sexual violence. Based upon these findings, I emphasize that reparations are value-loaded and inevitably depend on local gendered, cultural and societal contexts.